How Does Internationalization Affect The Performance Of Indonesian Family Firms With CEOs’ Demographics As Moderators? - Wisudanto Mas Soeroto; Madyan, Muhammad; Daffa, Muhammad; Rahmadani Setiawan, Wulan (Thailand and The World Economy, 2024)
This article examines how internationalization affects Indonesian family firm performance, with CEO demographics as moderators. We use least-squares regression using 1,097 observations of family firms listed in Indonesia from all industries except the financial sector from 2015 to 2021. The results indicate a positive relationship between internationalization and long-term firm performance, as measured by Tobin’s Q. We also demonstrate that demographic characteristics of CEOs, such as education level, tenure, age, and international experience, can weaken the relationship between internationalization and firm performance. This study provides a novel moderation of characteristics of demographic CEO between internationalization and firm performance. These findings will interest politicians and firms when recruiting CEOs because demographics affect internationalization decisions that affect firm performance. The study has been limited to using only one measure of internationalization and six CEO demographic characteristics.